Optimizing Kitabah Learning with a Scientific Approach: The Effectiveness of Word Square Media in Improving Writing Creativity at Mts Ittihadul Ulum Lubuklinggau - Yusnida, Yusnida; Mukmin, Mukmin; Hidayah, Nurul (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2025)
This study aims to examine the effectiveness of Word Square media with a scientific approach in improving Arabic writing creativity (kitabah) of MTs Ittihadul Ulum Lubuklinggau students. The main problem faced is the conventional learning approach that does not involve students actively so that it has an impact on low writing creativity. The research method used mixed method with exploratory sequential model. The quantitative design used a pseudo-experiment with experimental and control groups. Data were collected through tests (pretest-posttest), observations, and interviews. Quantitative data analysis used the Mann-Whitney test, while qualitative data were analyzed thematically. The results showed a significant increase in the experimental class with an average posttest score of 78.5 compared to the control class of 69.5. Asymp. Sig value of 0.66